2019
DOI: 10.3389/fenvs.2019.00128
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Field Sampling and Soil Survey Database for Spatial Heterogeneity in Surface Soil Granulometry: Implications for Ecosystem Services Assessment

Abstract: Lithospheric-derived resources such as soil texture and coarse fragments are key soil physical properties that contribute to ecosystem services (ES), which can be valued based on "soil" or "mineral" stocks. Soil survey data provides an inexpensive alternative to detailed field measurements which are often labor-intensive, time-consuming, and costly to obtain. However, both field and soil survey data contain heterogeneous information with a certain level of variability and uncertainty in data. This study compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…There are numerous challenges in using appropriate soil data sources and valuation methods for soil properties. For example, Mikhailova et al (2019) [47] compared field sampling and soil survey database for spatial heterogeneity in surface granulometry (sand, silt, and clay) for potential use in ES/ED valuations and concluded that field sampling provided more detailed information. The same study revealed that soil texture and coarse fragments are lithospheric-derived resources (Figure 1) and can be valued based on "soil" or "mineral" stock.…”
Section: Examples Of Parametric Pedodiversity and Ecosystem Servicesmentioning
confidence: 99%
“…There are numerous challenges in using appropriate soil data sources and valuation methods for soil properties. For example, Mikhailova et al (2019) [47] compared field sampling and soil survey database for spatial heterogeneity in surface granulometry (sand, silt, and clay) for potential use in ES/ED valuations and concluded that field sampling provided more detailed information. The same study revealed that soil texture and coarse fragments are lithospheric-derived resources (Figure 1) and can be valued based on "soil" or "mineral" stock.…”
Section: Examples Of Parametric Pedodiversity and Ecosystem Servicesmentioning
confidence: 99%